Precalculus: Mathematics for Calculus, 7th Edition

Published by Brooks Cole
ISBN 10: 1305071751
ISBN 13: 978-1-30507-175-9

Chapter 1 - Section 1.3 - Algebraic Expressions - 1.3 Exercises: 85

Answer

$x^{3}+4x^{2}+x+4=(x^{2}+1)(x+4)$

Work Step by Step

$x^{3}+4x^{2}+x+4$ Group the first two terms and the last two terms together: $x^{3}+4x^{2}+x+4=(x^{3}+4x^{2})+(x+4)=...$ Take out common factor $x^{2}$ from the first parentheses: $...=x^{2}(x+4)+(x+4)=...$ Now, finish the factoring process by taking out common factor $(x+4)$: $...=(x^{2}+1)(x+4)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.